Outbreak of Campbell de Morgan Spots. Issue 5693 (14th February 1970) - Seville, R. H.; Rao, P. S.; Hutchinson, D. N.; Birchall, G.
Abstract : An outbreak of small angiomatous lesions with the same clinical and histological features as Campbell de Morgan spots in adults is described. No infective agent was discovered, but their number was found to increase as the ambient temperature rose.